MicroRNAs in autoimmune rheumatic diseases - G.D. Sebastiani; C. Giannitti; E. Balistreri; M. Galeazzi (PAGEPress Publications, 2012)
The etiology of autoimmune diseases remains largely unknown. In recent years, besides genetic factors, several studies proposed that the epigenome may hold the key to a better understanding of autoimmunity initiation and perpetuation. More specifically epigenetic regulatory mechanisms comprise DNA methylation, a variety of histone modifications, and microRNA (miRNA) activity, all of which act upon gene and protein expression levels. In particular it is well known that epigenetic mechanisms are important for controlling the pattern of gene expression during development, the cell cycle, and the response to biological or environmental changes. In the present review a description of the most frequent epigenetic deregulations, in particular the role of miRNA, in rheumatic autoimmune disorders will be analyzed.